Engaging the Bajau laut: Establishing affinity with the community through the use of their language - Sanen Marshall; Saidatul Nornis Hj. Mahali (Pusat Penataran IImu dan Bahasa, 2021)
The Bajau Laut, also known as ‘Sea Gypsies,’ are one of the ethnic groups that are difficult to research because of their remote locations and habitations. The researcher provides a list of these habitations and the varying degrees of access afforded to them. The Bajau language is one of the key methods for engaging them. This paper discusses how researchers can utilise the Bajau language to establish initial familiarity with Bajau individuals and communities. The researcher describes the Bajau Language in brief and lists down words, phrases, and the functions that they play in Bajau Laut society. The author goes on to describe how the language that is spoken by one or two other coastal ethnic groups in Sabah is generally spoken and/or understood by the Bajau Laut The researcher considers several specific sets of words in the Bajau language, in particular those dealing with kinship, security, food, health, family origins and others.